Innovative Technology for Making Solid Soap from Used Cooking Oil as a Solution to the Problem of Household Waste and Home Industry Barukan Village, Manisrenggo, Klaten, Central Java : Teknologi Inovasi Pembuatan Sabun Padat Dari Minyak Jelantah Sebagai Solusi Permasalahan Limbah Rumah Tangga Dan Home Industri Desa Barukan, Manisrenggo, Klaten, Jawa Tengah - Riansih, Chici; Purwanti, Ratih; Ratnaningsih, Dwi; Susilani, Amalina Tri (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
Continuous disposal of used cooking oil waste that is not environmentally sound can have a negative impact on the environment and human survival. The community needs to be introduced to innovation in order to minimize household waste, especially those that have the potential to damage the environment. Used cooking oil waste produced from the rest of the frying pan in the kitchen can be reprocessed into soap. This community service aims to foster public awareness of the environment and provide skills training and assistance in soap making in efforts to control environmental pollution. The method used used used cooking oil waste treatment system based on zero waste industry. The first activity was education on October 4, 2023 and evaluation of activities on October 20, 2023 in Barukan Village, Manisrenggo, Klaten, Central Java, the number of participants was 50 people. The dedication that has been done has succeeded in making people more concerned about the environment and skilled in making solid soap from used cooking oil. The soap made is then packaged and labeled so that it becomes an economically valuable souvenir product and can then be marketed by implementing appropriate technology